Community Attitude and Behavior Toward Village Forest Management Plan in Central Sulawesi, Indonesia - Hendra Pribadi; Adam Malik; Golar Golar; Massiri Massiri; Abdul Rahman; Arman Maiwa; Sudirman Dg (Jurnal Ilmu Kehutanan, 2023)
Social forestry programs, including village forest schemes, were anticipated to increase the local community income, but the implementations often differed from the plans. Therefore, this research aimed to determine the attitude and behavior of LPHD members toward village forest management in Central Sulawesi by analyzing their beliefs and evaluation values. The results showed that the forest attribute had the highest value, which indicated that the village forest offered numerous opportunities to enhance the community's welfare. In addition, the attitude value was consistent with the behavior analysis, resulting in a positive value of 0.74. This value indicated that LPHD members agreed with the village forest management in Central Sulawesi and actively participated in the implementation.